2014
DOI: 10.1007/s12032-014-0414-9
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 2 is involved in vasculogenic mimicry formation by targeting VEGFR2 activation in colorectal cancer

Abstract: The mammalian peroxiredoxin 2 (Prdx2) is a member of thiol-dependent antioxidant proteins and plays an important role in the progression of colorectal cancer (CRC). The aim of this study was to confirm the role of Prdx2 in formation of VM and progression of CRC. Immunohistochemistry and CD34/periodic acid Schiff double staining were performed to explore the expression of Prdx2 and VM formation in 70 CRC tissues, and there was a positive correlation between Prdx2 expression and VM formation by the Pearson corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…In contrast to CSCs, we found that Parental cells, in line with their inability to form tube‐like structures on either Matrigel or collagen I, secreted a higher number of antiangiogenic factors and these were up‐regulated when they grew on collagen I. Importantly, the only factor to have an increased secretion on Matrigel was VEGF, the proangiogenic factor par excellence known to stimulate vasculogenesis and angiogenesis through both autocrine and paracrine mechanisms . Indeed, VEGF was secreted from Parental cells at the same level as in CSCs (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast to CSCs, we found that Parental cells, in line with their inability to form tube‐like structures on either Matrigel or collagen I, secreted a higher number of antiangiogenic factors and these were up‐regulated when they grew on collagen I. Importantly, the only factor to have an increased secretion on Matrigel was VEGF, the proangiogenic factor par excellence known to stimulate vasculogenesis and angiogenesis through both autocrine and paracrine mechanisms . Indeed, VEGF was secreted from Parental cells at the same level as in CSCs (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…7 VM had been found to evaluate in various aggressive cancers, including colorectal cancer, 8 breast cancer, 9 melanoma, 10 and head and neck squamous cell carcinoma, 11 suggesting that it was a novel hallmark of cancer. 7 VM had been found to evaluate in various aggressive cancers, including colorectal cancer, 8 breast cancer, 9 melanoma, 10 and head and neck squamous cell carcinoma, 11 suggesting that it was a novel hallmark of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A series of researches have concluded that PRDXs are involved in some particular pathological conditions such as cancer, inflammatory diseases and neurodegenerative diseases [25]. In particular, PRDX isoforms were regarded as good therapeutic targets in various type of cancers including prostate cancer [26], colorectal cancer [13, 20, 21], glioblastoma [27], lung cancer [28] and ovarian cancer [29, 30]. Currently, a total of six PRDXs isozymes (PRDX 1–6) have been identified in mammalian systems, and PRDX2 belongs to typical 2-Cys group with two conserved cysteine residues [31].…”
Section: Discussionmentioning
confidence: 99%
“…Later, our another research showed that inhibiting PRDX2 expression augmented apoptosis, decreased cell growth, and increased endogenous ROS production through down-regulating Wnt/beta-catenin signaling pathway [20]. In addition, down-regulation PRDX2 expression inhibited VEGF mimicry formation of HCT116 cells through targeting VEGFR2 activation in colorectal carcinoma [21]. However, the clinical implication of the protein expression of PRDX2 in CRC has not been reported.…”
Section: Introductionmentioning
confidence: 99%